ANALISIS PELAYANAN, SUASANA, DAN VARIASI MENU TERHADAP KEPUTUSAN PEMBELIAN PADA CAFE FAMELIZA BARON NGANJUK - Jamilah, Intan Nadhifatul (Prosiding Seminar Nasional Manajemen, Ekonomi dan Akuntansi, 2022)
This study to determine the level of purchasing decisions by analyzing the factors that influence the level of purchasing decisions including service, cafe atmosphere, and variations in the menu cafe fameliza baron nganjuk. this research method using quantitative methods, with data collection techniques through observation, interviews, and distributing questionnaires. Sampling and research using non-probabability sampling. The population in this study were all customers cafe fameliza baron nganjuk, the number of which was not limited or unknown. The sample used is 40 respondents by using purpososive sampling technique. data collection technique used questionnaire which was then analyzed using SPSS software for windows version 25. The analysis used in this study was validity test, reliability test, classical assumption test, multiple linear regression test, coefficient of determination (R2), T test, F test. The results of study indicate that service factors, cafe atmosphere, and menu variations significantly influence purchasing decisions Cafe Fameliza Baron Nganjuk.